Barium titanate thin films deposited by electrophoresis on p-doped si(001) substrates - Barbosa, José Gusman (2011)
Barium titanate (BaTiO3) thin films have been prepared by electrophoretic deposition on p-doped and platinum covered silicon (Si) substrates. Their structure, nanostructure and dielectric properties were characterized. The as-deposited films were polycrystalline and composed by barium titanate nanograins with an average grain size ~9 nm. Annealing at high temperatures promoted grain growth, so that the samples annealed at 600 ºC presented average grain sizes ~24 nm. From Raman spectroscopy measurements it was found that the tetragonal (ferroelectric) BaTiO3 phase was stabilized on the films. Also, at higher annealing temperatures, cation disorder was reduced on the films. From measurements of the temperature dependence of the dielectric permittivity the corresponding paraelectric-ferroelectric phase transition was determined. The observed transition temperature (~100ºC) was found to be below the BaTiO3 bulk or thick film values, due to the small nanosized grains composing the films.